2016
DOI: 10.1128/jb.00348-16
|View full text |Cite
|
Sign up to set email alerts
|

Partial Diversity Generates Effector Immunity Specificity of the Bac41-Like Bacteriocins of Enterococcus faecalis Clinical Strains

Abstract: Bacteriocin 41 (Bac41) is the plasmid-encoded bacteriocin produced by the opportunistic pathogen Enterococcus faecalis. Its genetic determinant consists of bacL 1 (effector), bacL 2 (regulator), bacA (effector), and bacI (immunity). The secreted effectors BacL 1 and BacA coordinate to induce the lytic cell death of E. faecalis. Meanwhile, the immunity factor BacI provides self-resistance to the Bac41 producer, E. faecalis, against the action of BacL 1 and BacA. In this study, we demonstrated that more than hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In line with the hypothesis of different routes of hospital adaptation, we observed some plasmidome population core genes that are only present as core in some plasmidome populations associated with hospitalized patients. We observed the presence of a bacteriocin with homology to BacA in populations 5, 7, and 8 and previously described as a plasmid-borne bacteriocin in E. faecalis (29). BacA can act as a more evolved toxin-antitoxin system in which not only daughter cells but also cells from the same generation not bearing the BacA plasmid are excluded.…”
Section: Figsupporting
confidence: 68%
See 1 more Smart Citation
“…In line with the hypothesis of different routes of hospital adaptation, we observed some plasmidome population core genes that are only present as core in some plasmidome populations associated with hospitalized patients. We observed the presence of a bacteriocin with homology to BacA in populations 5, 7, and 8 and previously described as a plasmid-borne bacteriocin in E. faecalis (29). BacA can act as a more evolved toxin-antitoxin system in which not only daughter cells but also cells from the same generation not bearing the BacA plasmid are excluded.…”
Section: Figsupporting
confidence: 68%
“…BacA can act as a more evolved toxin-antitoxin system in which not only daughter cells but also cells from the same generation not bearing the BacA plasmid are excluded. Furthermore, it was demonstrated that plasmid dissemination was more prominent under conditions of fluctuations in the population of E. faecium, since BacA activity exclusively affects dividing cells (29). We also observed a complete phosphotransferase system putatively involved in mannose/fructose/sorbose utilization present in the plasmidome cores of populations 6 and 7.…”
Section: Figmentioning
confidence: 56%
“…These adaptations include the presence of CRISPR‐Cas in the chromosome (Palmer and Gilmore, ; Price et al ., ), restriction‐modification (RM) and anti‐RM systems, which would act against certain plasmids (e.g. pCF10); or lineage‐specific bacteriocins carried by pheromone‐responsive plasmids (Kurushima et al ., ) or conjugative transposons (Tn 916 ‐like elements) that might influence the transfer of genetic material within and between lineages (Manson et al ., ; Laverde Gomez et al ., ; León‐Sampedro et al ., ; Price et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of plasmid genes specifically present in each of the isolation sources revealed the presence of a widely-spread bacteriocin-like gene (bacA) in our set of hospitalized isolates that was rarely present in other isolation sources. As previously reported for E. faecalis, bacA can act as a sophisticated toxin-antitoxin system, in which not only daughter but also co-existing bacA plasmidfree cells are excluded from the population (Kurushima et al 2016). As such, this bacA gene may have contributed to the ecological dominance of the distinct subpopulation of E. faecium hospital isolates in patients.…”
Section: Discussionmentioning
confidence: 54%
“…Plasmidomes of hospitalized patient isolates were enriched (Specificity & Sensitivity > 80%) for a large pool of genes (n = 589, OR > 1) ( Supplementary Fig. S8) with a variety of functions, including a bacteriocin-like protein (bacA) previously described as plasmid-related in E. faecalis (Kurushima et al 2016) and antibiotic-resistance related genes such as aacA-aphD or efflux permease ABC transporters ( Supplementary Table S6). Poultry and pig isolates showed a pool of 155 and 100 enriched plasmid genes (OR > 1; Specificity & Sensitivity > 80%), respectively ( Supplementary Fig.…”
mentioning
confidence: 99%